QUALITY OF LIFE ASSESSMENT IN PATIENTS WITH HEMOBLASTOSIS WITH IMPAIRMENT OF NERVOUS SYSTEM - O.O. Piddubna; N.V. Lytvynenko (Проблеми екології та медицини)
Neurological disorders in oncohematologic diseases are among the secondary impairment of the nervous system and combine pathological conditions of the nervous system with different mechanisms of development and localization associated with neoplastic diseases of the blood system, which significantly exacerbates the course of the basic disease. The study of quality of life (QOL) in medicine provides information about the state of physical, emotional and psychological functioning of patient, allows to examine the dynamics of the disease and to evaluate the effectiveness of treatment. We investigated quality of life in patients with hemoblastosis and syndromologic features of the nervous system impairment. To accomplish this aim we conducted a complex of clinical and neurological examination with research of QOL by the questionnaire SF-36 in 77 patients with hemoblastosis. Depending on the type of underlying disease, patients were divided into 3 groups: patients with chronic lymphocytic leukemia (27 persons), patients with multiple myeloma (24 people) and patients with chronic myeloid leukemia (26 people). Control group consisted of 23 patients with appropriate age and gender allocation. According to the results of research, a significant decrease in all indicators of questionnaire SF-36 has been revealed in patients with hemoblastosis and impairment of the nervous system as compared to the control group. Impairment of the nervous system in patients with hemoblastosis was due to the influence of various aggregate factors, one of which can be regarded as lesion of the central and peripheral nervous system.